Regulation of Thromboxane Receptor Signaling at Multiple Levels by Oxidative Stress-Induced Stabilization, Relocation and Enhanced Responsiveness - Ball, Stephen K.; Field, Mark C.; Tippins, John R. (PLOS ONE, 2010)
Background Thromboxane A2 (TxA2) is a major, unstable arachidonic acid metabolite, and plays a key role in normal physiology and control of vascular tone. The human thromboxane receptor (TPβ), expressed in COS-7 cells, is located predominantly in the endoplasmic reticulum (ER). Brief hydrogen peroxide exposure increases the efficiency of translocation of TPβ from the ER into the Golgi complex, inducing maturation and stabilization of TPβ. However, the ultimate fate of this post-ER TPβ pool is not known, nor is its capacity to initiate signal transduction. Here we specifically assessed if functional TPβ was transported to the plasma membrane following H2O2 exposure. Results We demonstrate, by biotinylation and confocal microscopy, that exposure to H2O2 results in rapid delivery of a cohort of TPβ to the cell surface, which is stable for at least eight hours. Surface delivery is brefeldin A-sensitive, indicating that translocation of this receptor cohort is from internal pools and via the Golgi complex. H2O2 treatment results in potentiation of the increase to intracellular calcium concentrations in response to TPβ agonists U46619 and 8-iso PGF2α and also in the loss of ligand-dependent receptor internalization. Further there is increased responsiveness to a second application of the agonist. Finally we demonstrate that the effect of H2O2 on stimulating surface delivery is shared with the FP prostanoid receptor but not the EP3 or EP4 receptors. Conclusions/Significance In summary, brief exposure to H2O2 results in an immediate and sustained increase in the surface pool of thromboxane receptor that is capable of mediating a persistent hyper-responsiveness of the cell and suggests a highly sophisticated mechanism for rapidly regulating thromboxane signaling.